High-resolution mapping of molecules in an ionic liquid via scanning transmission electron microscopy. (28th November 2017) - Miyata, Tomohiro; Mizoguchi, Teruyasu
Abstract : Real-space distribution of molecules in an ionic liquid C2mimTFSI has been visualized at an atomic scale using scanning transmission electron microscopy. Anion molecules (TFSI-) were experimentally observed bright in the liquid layer, which was confirmed with an image simulation. Abstract: Understanding structures and spatial distributions of molecules in liquid phases is crucial for the control of liquid properties and to develop efficient liquid-phase processes. Here, real-space mapping of molecular distributions in a liquid was performed. Specifically, the ionic liquid 1-Ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (C2 mimTFSI) was imaged using atomic-resolution scanning transmission electron microscopy. Simulations revealed network-like bright regions in the images that were attributed to the TFSI − anion, with minimal contributions from the C2 mim + cation. Simple visualization of the TFSI − distribution in the liquid sample was achieved by binarizing the experimental image.